Spatio-temporal structure of the urban thermal environment in Beijing based on an empirical orthogonal function. Issue 2 (3rd July 2018) - Qiao, Zhi; Wu, Chen; Huang, Ningyu; Xu, Xinliang; Sun, Zongyao; Sun, Xihua
ABSTRACT: An understanding of the spatio-temporal structure of the urban thermal environment (UTE) is important for determining the formation mechanism of the urban heat island (UHI) effect. The empirical orthogonal function (EOF) was applied in this study to analyse the spatio-temporal characteristics and trends of the UTE in summer in the Beijing metropolitan area using temperature data obtained from meteorological observatories between 1978 and 2010. The overall summer temperature had a three-step distribution from southwest to northeast cross the Beijing metropolitan area, with a dual-core high-temperature region in the central city and the Capital International Airport.